Did Immigrant Arrest Rates Change During the Trump Administration? Evidence From California and Texas - Light, Michael T. (Crime & delinquency, 2024)
Despite substantial legal and policy debates, whether immigrant arrest rates changed during the Trump presidency remains surprisingly understudied. This is partially because immigration status is rarely available in crime data. We address this gap by applying difference-in-differences (DD) and difference-in-difference-in-differences (DDD) estimations to detailed arrest data from Texas and California from 2015 to 2018. We find little evidence, descriptive or otherwise, to suggest that the transition from the Obama to the Trump administration had a meaningful impact on immigrant arrests, whether measured as violence, property, drug, or traffic offenses. These results suggest that the immigration enforcement initiatives under President Trump did not deliver on their crime reduction pledges, but they also provide little evidence of over-policing of immigrants in discretionary actions such as traffic arrests.